A novel simple disposition index (SPINA‐DI) from fasting insulin and glucose concentration as a robust measure of carbohydrate homeostasis - Johannes W. Dietrich; Assjana Abood; Riddhi Dasgupta; Shajith Anoop; Felix K. Jebasingh; R. Spurgeon; Nihal Thomas; Bernhard O. Boehm (Journal of Diabetes)
Abstract Aims The widely used dynamic disposition index, derived from oral glucose tolerance testing, is an integrative measure of the homeostatic performance of the insulin‐glucose feedback control. Its collection is, however, time consuming and expensive. We, therefore, pursued the question if such a measure can be calculated at baseline/fasting conditions using plasma concentrations of insulin and glucose. Methods A new fasting‐based disposition index (structure parameter inference approach‐disposition index [SPINA‐DI]) was calculated as the product of the reconstructed insulin receptor gain (SPINA‐GR) times the secretory capacity of pancreatic beta cells (SPINA‐GBeta). The novel index was evaluated in computer simulations and in three independent, multiethnic cohorts. The objectives were distribution in various populations, diagnostic performance, reliability and correlation to established physiological biomarkers of carbohydrate metabolism. Results Mathematical and in‐silico analysis demonstrated SPINA‐DI to mirror the hyperbolic relationship between insulin sensitivity and beta‐cell function and to represent an optimum of the homeostatic control. It significantly correlates to the oral glucose tolerance test based disposition index and other important physiological parameters. Furthermore, it revealed higher discriminatory power for the diagnosis of (pre)diabetes and superior retest reliability than other static and dynamic function tests of glucose homeostasis. Conclusions SPINA‐DI is a novel simple reliable and inexpensive marker of insulin‐glucose homeostasis suitable for screening purposes and a wider clinical application.